Clinical Features, Laboratory Parameters, Treatment and Outcome analysis of COVID-19 Patients admitted to a Referral Hospital at Nepalese Terai Region during Second Wave - Mishra, Raman; Singh, Jitendra Kumar; Jha, Birendra Kumar; Priya, Kusum; Khanal, Amrit; Anand, Abhinav; Yadav, Ajay Kumar (Janaki Medical College Journal of Medical Science, 2023)
Background & Objective: COVID-19 pandemic has tested health care systems worldwide. The massive wave of infection in Nepal between March to April 2021 overwhelmed the health care institutions throughout the country. This study describes the demographic, clinical, laboratory parameters and outcome of patients hospitalized in a secondary level facility during second wave of infection. Material and Methods: The data was extracted from admitted patients at Janaki Health Care and Teaching Hospital (JHCTH) with COVID-19, between 9th April to 14th June 2021. Demographic, clinical, laboratory parameters, treatment and outcome were recorded from the medical records and analyzed. Results: Out of 122 admitted patients,11%, 18.03%, 33.60% and 35.24% presented with mild, moderate, severe and critical illnesses respectively, with the median saturation of peripheral oxygen (SPO2) at admission was 89(34-99)% and 17 deaths were recorded a mortality rate of 20.4%.A significantly high mortality rate was found among ventilated patients (73.3%), against non ventilated (7.2%). Mortality rates among critically and severely ill patients were 38.46 % and 6.9% respectively. Mean C reactive protein (CRP) was 51.13(±30.50)mg/dl. Statistically significant CRP levels were observed in patients who presented with mild illness (32.53±10.85 mg/dl) and those who died in hospital (61.08±30.00 mg/dl). Remdesivir use did not offer any mortality benefit. Conclusion: A very high mortality rate (20.40%) observed in this study due to COVID-19 in hospitalized patients, may be associated with a high proportion of severe and critical cases (68.70%) admitted. Further upgrading of health resources should be prioritized to manage severe COVID-19 related mortalities, because of the possibility of a future waves.